2011
DOI: 10.1016/j.tjog.2011.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Meigs’ syndrome with elevated serum cancer antigen 125 levels in a case of ovarian sclerosing stromal tumor

Abstract: SCT is a benign ovarian tumor and complete excision is curative. We also review all 37 cases and discuss possible mechanisms of Meigs' syndrome and elevated serum CA 125 level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 21 publications
2
24
0
4
Order By: Relevance
“…A significant linear correlation between volume of pleural effusion and serum Ca125 values has been demonstrated in both benign and malignant diseases. 2 Similar correlation has been demonstrated between CA125 elevation and volume of ascites in Meigs syndrome.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…A significant linear correlation between volume of pleural effusion and serum Ca125 values has been demonstrated in both benign and malignant diseases. 2 Similar correlation has been demonstrated between CA125 elevation and volume of ascites in Meigs syndrome.…”
Section: Discussionsupporting
confidence: 58%
“…Since then 38 cases have been reported, including four with SSTs. 2 We report fifth case of Meigs syndrome associated with SST of the ovary.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…13 Similar correlation has been demonstrated between CA125 elevation and volume of ascites in Meigs syndrome. Our patient had a raised level of CA125 of 98 IU/ml with mild ascites and pleural effusion.…”
Section: Figure 4: Round Cells With Clear Cytoplasm (Hande 400x)supporting
confidence: 58%
“…15,16 Ascites is present in 10-15% of patients with ovarian fibroma, and pleural effusion is present in 1%,especially in cases showing large lesions. 17,18 However, most patients with ovarian fibromas remain asymptomatic, with the tumor often progressing to a large pelvic mass. 18 The immunohistochemical study for CA-125 suggested that serum elevation of CA-125 antigen in patients with Meigs' syndrome is caused by mesothelial expression of CA-125 rather than by fibroma.…”
Section: Discussionmentioning
confidence: 99%